Understanding barriers and facilitators to non-pharmaceutical chronic pain research engagement among people living with chronic pain in the UK: a two-phase mixed-methods approach - Daniel Baker; Kirralise Hansford; Anna E Crossland; Catherine Preston; Kirsten J McKenzie (BMJ Open)
Objectives Chronic pain treatment engagement is dominated by pharmaceutical methods, while previous research has assessed barriers to uptake of non-pharmaceutical treatments, there has not been research one step earlier in the treatment development pipeline; assessing barriers to take part in research that develops non-pharmaceutical chronic pain treatment methods.Design A two-phase approach was used to assess barriers and facilitators to research participation for people living with chronic pain. Online focus groups were run in phase 1, generating qualitative data, while phase 2 used the themes identified within phase 1 to assess agreement and disagreement.Setting Participants consisted of people with chronic pain across the UK.Participants 36 participants with chronic pain conditions (defined as any pain lasting or recurring for more than 3 months) were recruited for phase 1. Seven participants could not attend their focus group or a subsequent session, leaving a final sample size of 29 participants (83% female, 17% male; age=20–78 years, M=44.3 years). Phase 2 consisted of 103 participants (89% female, 10% male, 1% prefer not to say; age=20–80 years, M=46.6 years).Results Phase 1 identified the largest barrier to be ‘distrust’, relating to a distrust of medical and research professionals, distrust of confidentiality assurances and distrust that the research would have an impact. The greatest facilitator identified was ‘improved accessibility’, which related to the accessibility of the research environment, the type of research being conducted and accessible advertisement of the research within trusted settings. Phase 2 found around 80% agreement with all facilitator themes and a mix of opinions regarding barrier themes, highlighting the individuality of barriers experienced when living with chronic pain.Conclusions Addressing the barriers and implementing the facilitators identified here ensures that patient participants are comfortable and safe within research environments. Furthermore, this project provides recommendations for researchers to follow to help increase patient engagement in research studies.